Towards Gender Equality in the Music Industry: Education, Practice and Strategies for Change - Strong, Catherine; Raine, Sarah (Bloomsbury Publishing USA, 2019)
Gender inequality is universally understood to be a continued problem in the music industry. This volume presents research that uses an industry-based approach to examine why this gender imbalance has proven so hard to shift, and explores strategies that are being adopted to try and bring about meaningful change in terms of women and gender diverse people establishing ongoing careers in music. The book focuses on three key areas: music education; case studies that explore practices in the music industry; and activist spaces. Sitting at the intersection between musical production, the creative industries and gender politics, this volume brings together research that considers the gender politics of the music industry itself. It takes a global approach to these issues, and incorporates a range of genres and theoretical approaches. At a time when more attention than ever is being paid to gender and music, this volume presents cutting edge research that contributes to current debates and offers insights into possible solutions for the future.
Keywords: Music / Business Aspects; Music / Philosophy & Social Aspects; Social Science / Gender Studies; Social Science / Women's Studies

Counting the music industry: the gender gap - Bain, V (Counting the music, 2019)

Tackling gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, Sam (International Journal of Cultural Policy, 2019)
Cross-disciplinary research has highlighted the persistence of gender inequalities across music scenes. However, the way in which cultural policy shapes responses to gender inequalities in music has been relatively underexplored. This article draws on research from Swedish and UK contexts, supporting analysis with reference to 9 key-stakeholder interviews from both. Comparing perspectives from ‘more’ and ‘less’ gender-equal contexts, with sufficiently different cultural policy traditions, the article explores how responses to gender inequalities in music are influenced by ‘cultural democratic’ and ‘arm’s length’ approaches. It demonstrates that, as a result of these traditions, there is a comparatively more interventionist approach in Sweden at a national level, whereas the lack of central government response in the UK has encouraged more market-oriented solutions. It suggests that this ‘arm’s length’ approach necessitates different grassroots organisational strategies in order to affect change but notes that these, alongside austerity agendas, are insufficient in the long term.
Keywords: Music policy; arm’s length; gender inequalities; interventionist; market-oriented

Female Brass Musicians Address Gender Parity, Gender Equity, and Sexual Harassment: A Preliminary Report on Data from the Brass Bodies Study - Schmalenberger, Sarah; Maddox, Patricia (Societies, 2019)
The Brass Bodies Study is an exploratory cross-sectional study designed to describe and understand the experience of female brass players. This report discusses selected data from close-ended and open-ended responses to questions regarding gender equity, parity, and sexual harassment within a web-based survey that launched the first phase of the study. The survey queried subjects’ physical changes to their brass playing due to various catalysts: life-cycle events; injury, illness, harassment, mental health, racism, and homophobia. The survey instrument further queried whether subjects received support about these changes and the effectiveness of support. The following report discusses survey responses to questions about gender parity and changes to brass playing due to sexual harassment. Additional qualitative data were generated from open-ended questions in the survey and were qualitatively coded and thematically presented to supplement the descriptive statistics provided. The information presented explores and defines salient items and themes of a population that is under researched with the hopes of generating hypotheses for continued research.
Keywords: Brass Bodies Study; Myriam; female brass players; female musicians; music workplace climate

Consentability: Consent and its Limits - Kim, Nancy S. (Cambridge University Press, 2019)

Violence in the mosh pit: assault within the Australian punk scene - Barnes, Ash; White, Rob (Current Issues in Criminal Justice, 2019)
The mosh pit is a unique crowd formation where audience members dance aggressively to engage with the music, the performers and each other. However, in this space, Australian punks may experience violations of bodily integrity. Multiple levels and types of transgression occur, as members break with mosh pit ethics by engaging in unwanted and unlawful sexual and physical violence. This case study provides an example of how group normative behaviour is confounded in liminal spaces – how transgression within such spaces undermines the supposed freedom experienced by its participants. Whilst the mosh pit is perceived to be a site governed by its own particular ethics, some defy these in word and practice. The rules of engagement are ambiguous, and offenders are able to rationalise their harms through neutralisation techniques and the diffusion of blame and responsibility. The consequence is that more often than not, offenders can use the unique physical nature of the mosh pit to execute personal vendettas and engage in intentional violence such as ‘crowd killing’ and sexual assault, with little social and legal consequence. Moreover, a certain culture of denial permeates participant responses to these issues. Throughout it all, the violence occurring has a decidedly masculine basis, reflecting overarching gender differences in interpersonal violence generally.
Keywords: assault; cultural criminology; denial; mosh pit; punk scene

Women composers’ use of online communities of practice to build and support their careers - Hennekam, Sophie; Macarthur, Sally; Bennett, Dawn; Hope, Cat; Goh, Talisha (Personnel Review, 2019)
Purpose The purpose of this paper is to examine women composers’ use of online communities of practice (CoP) to negotiate the traditionally masculine space of music composition while operating outside its hierarchical structures. Design/methodology/approach The authors employed a mixed methods approach consisting of an online survey (n=225) followed by 27 semi-structured in-depth interviews with female composers to explore the concept and use of CoP. Content analysis was used to analyze the survey responses and interpretative phenomenological analysis was used to interpret respondents’ lived experiences as relayed in the interviews. Findings The findings reveal that the online environment can be a supportive and safe space for female composers to connect with others and find support, feedback and mentorship, increase their visibility and develop career agency through learning and knowledge acquisition. CoP emerged as an alternative approach to career development for practicing female music workers and as a tool which could circumvent some of the enduring gendered challenges. Originality/value The findings suggest that online CoP can have a positive impact on the career development and sustainability of women in male-dominated sectors such as composition.
Keywords: Career progression; Communities of practice; Creative industries; Gender; Mixed methodologies; Myriam; Women composers; music industry

Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events - Fileborn, B.; Wadds, P.; Barnes, A. (2019)
Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events
Keywords: Camille

Carefree or Controlled? Understanding the Night-Time Economy - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
The term ‘Night-Time Economy’ was coined in the late twentieth century (Shaw 2014) in town planning circles, and increasingly used into the twenty-first century to describe the expanding number of pubs, bars and clubs concentrated in city centres and targeting predominantly 18–24-year-olds (Roberts 2006: 332). But what exactly is the Night-Time Economy, and what role does it play in the lives of young women today? How has it changed as a site of leisure, and what does it mean to say that neoliberal forces have played a role in shaping it? What do we mean by the supposed ‘feminisation’ of the NTE, and what are the implications of this process for the ways that women engage with these spaces? This chapter charts the development of the NTE in the UK and the rise of the ‘24-hour city’, highlighting the ways in which neoliberal ideals have shaped both the landscape of the NTE and the types of behaviours and consumption practices that are expected within it. Such considerations are important for research that attends both to the wider social structures within the NTE and the individual specificities of the lives of young people as they participate in it. I will then explore the significance of space and place in research focusing on the NTE, situating the current study geographically and exploring Newcastle’s own NTE in more depth and detail.
Keywords: Charvis; Essex Girl; Geordie; Night-time Economy; Northern Identity

Conclusion - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As has become increasingly evident throughout this book, the girls’ night out clearly offers specific and nuanced ways in which to do femininities and friendships which are not present in other types of night out, and perhaps also specific types of pressures to do femininity. Whilst the NTE is increasingly recognised as a useful avenue through which to research young people’s lives, less attention has been given to the girls’ night out as a specific type of engagement with the NTE that may illuminate nuances in the ways in which young women ‘do’ gender and femininities. This book thus marks a unique contribution within a wider body of research on young people’s drinking and clubbing. This concluding chapter will pull together the main arguments outlined throughout this book, highlighting the tensions and contradictions embedded in young women’s negotiations of femininity and the ways in which these reflect the idea that the successful embodiment of ‘girly’ and ‘girliness’ is simultaneously something that is desired yet derided.
Keywords: Drinking Practices; Girly Girl; Research Young People; Time Girls; otheringOthering

Introduction - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
‘Going out’ is widely recognised as a central leisure activity in the lives of many young people (Chatterton and Hollands, Urban nightscapes: Youth cultures, pleasure spaces and corporate power. Routledge, 2003; Waitt et al., ‘The guys in there just expect to be laid’: Embodied and gendered socio-spatial practices of a ‘night out’ in Wollongong, Australia. Gender, Place & Culture, 18(2), pp. 255–275, 2011), and engaging in leisure practices in the Night-Time Economy (NTE) is likely to be an important part of women’s lives in the UK. Indeed, the ‘night on the town’ is framed in many research accounts as offering important opportunities for young women to relax, socialise with friends and escape from the often mundane realities of everyday life, work and other responsibilities (Guise and Gill, ‘Binge drinking? It’s good, it’s harmless fun’: A discourse analysis of accounts of female undergraduate drinking in Scotland. Health Education Research, 22(6), pp. 895–906, 2007; Jayne et al., Emotional, embodied and affective geographies of alcohol, drinking and drunkenness. Transactions of the Institute of British Geographers, 35(4), pp. 540–554, 2010). Yet, young women’s experiences of the NTE are also clearly shaped by neoliberal and gendered expectations around consumption, body work and self-regulation. In particular, it is important to explore in more depth how—within a supposed ‘post-feminist’ context—expectations around ‘appropriately’ feminine dress and behaviour may continue to shape the experiences of young women like Nicole in contemporary leisure spaces. But what does it actually mean and look like for young women to be ‘feminine’ today? Is this something that is relevant or important to them? How are tensions around girliness and femininity lived and negotiated in practice in women’s everyday lives? And crucially, is it still more difficult for some women to adopt ‘appropriately’ feminine identities than others? This book considers these questions and explores the ways in which women’s participation in the UK NTE continues to be constrained in a supposedly post-feminist society (Harris, Jamming girl culture: Young women and consumer citizenship. In A. Harris (ed.) All about the girl: Culture, power and identity. Routledge, 2004).
Keywords: Contemporary Femininity; Contextual Expectations; Feminine Identity; Night-time Economy (NTE); Nightlife Scene

‘It’s Girl Time’: Girliness and Friendships - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
With what Chatterton and Hollands call the ‘ritual descent’ (2002: 95) of young women into bars and clubs every weekend, we must take seriously young women’s participation in such spaces and explore further what role participating in the NTE plays in young women’s lives. Participating in the NTE has been increasingly recognised as an important component of the lives of many young women (Hollands 1995), and the participants in my study were no exception. Set against a backdrop of conflicting debates positioning the NTE as simultaneously a site of both pleasure and regulation, it is important to understand the value engaging with the NTE has for young women and the ways in which this can offer opportunities for ‘doing’ femininities or girliness and cementing friendships within these spaces. The girls’ night out represents a discreet and distinctive mode of engagement with the NTE, yet one that has received little attention in research, despite the fact that it is likely to reveal a huge amount about the individual and collective production and negotiation of femininities and friendships in nightlife venues. This chapter provides the backdrop for the remainder of the book by exploring what the girls’ night out means to young women and the central role it can play in the negotiation and maintenance of friendships and in doing ‘girly’. Whilst previous research has depicted friendships within the NTE as potentially shallow or instrumental and consumption practices as highly individualised, this chapter highlights the ways in which going out was described as an important and valued opportunity to maintain close female friendships, spend time together and enjoy opportunities to socialise and relax. I will also introduce some of the ways in which alcohol consumption was central to the young women’s negotiations of the NTE. Drinking could take on a particular role on the girls’ night out, where alcohol could function in the maintenance and cementing of friendships and the creation of intimacy (particularly when ‘pre-drinking’ at home). Consuming certain types of alcohol could also enable ‘girliness’ to be embodied in particular ways through certain consumption choices. I argue that the ‘girling’ of drinking and clubbing is particularly significant because alcohol consumption in public spaces has traditionally been recognised as a masculine pastime, rendering drinking and femininity fundamentally incompatible. If young women are able to rupture the linkages between public drinking and masculinity, they may be able to recast women’s presence and alcohol consumption in the contemporary NTE as feminine and respectable. I also explore the ways in which getting ready for a girls’ night offered further opportunities to do girliness collectively.
Keywords: Female Friends; Girlhood; Girly Girl; Time Girls; wineWine

‘People Don’t See You if You’re a Woman and You’re Not Really Dressed Up’: Visibility and Risk - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
Against a backdrop of research suggesting that young women are still expected to engage in active risk management on a night out (Brooks, ‘Guys! Stop doing it!’: Young women’s adoption and rejection of safety advice when socializing in bars, pubs and clubs. British Journal of Criminology, 51(4), pp. 635–651, 2011), this chapter will explore the centrality of understanding of space and visibility to young women’s negotiations of risk and safety in mainstream bars and clubs in Newcastle’s NTE. Visibility comes into play in two distinct ways here—firstly, as in the previous chapter, participants drew on narratives of ‘fitting in’, this time to describe the types of venues that felt comfortable and safe to them. Attending a venue where they felt out of place or ‘different’ to other patrons could leave women feeling exposed, visible and vulnerable, and these spaces were positioned as risky and dangerous. Secondly, women recognised that bars and clubs are spaces where ‘everyday’ experiences of heterosexualised violence are trivialised and normalised, and they managed their dress and appearance in particular ways in order to position themselves as less visible—or even invisible—to try to avoid ‘unwanted attention’ and harassment.
Keywords: Charvis; Posh People; Sexual Abuse Rape; Unwanted Attention; Working-class College Students

‘Rowdy…? That’s the Whole Point of Going on a Night Out’: Time Out, Transgression and Control - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As the previous chapter has highlighted, alcohol consumption plays an important role in the maintenance of friendships and in the individual and collective production of ‘girly’ or feminine identities in the NTE. Yet long-standing and pervasive images of alcohol consumption as a threat to femininity mean women’s negotiations of drinking continue to be fraught with tensions and ambivalences. In something of a paradox, ‘the contradictions engendered by post-feminist discourse constitute drunkenness as unfeminine, [yet] young women are enthusiastically exhorted to consume within the neoliberal culture of intoxication’ (Hutton et al. 2016: 82). In other words, to be a good, neoliberal citizen within leisure sites such as the NTE requires women to consume alcohol, yet the demands of femininity necessitate that they also show restraint. At the same time, the NTE is portrayed as a site where abandonment, hedonism and ‘rowdy’ behaviour are to an extent normalised, perhaps even encouraged, yet such behaviour ruptures traditional expectations of femininity as passive and ‘ladylike’. How do women negotiate and make sense of some of these tensions as they confront the ‘orderly disorder’ (Smith 2014: 2) of a typical night out? Is there a degree of acceptance of ‘rowdy’ or transgressive behaviour? And how does this sit alongside an expectation to be girly, as outlined in the previous chapter?
Keywords: Drinking Practices; Drunk Woman; Girly Girl; Kirsty; Transgressive Behavior

‘What Else About Her Is Fake?’: ‘Emphasised’ Femininity, Authenticity and Appearance - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
This chapter charts the ways in which young women’s negotiations of dress in the NTE are shaped by notions of visibility and authenticity and also by class. I explore the ways in which an exaggerated or emphasised mode of femininity is normalised to an extent within the NTE and highlight some of the pleasures and values young women found in their negotiations of femininity through dress, whether wholeheartedly embracing or ‘flashing’ femininity. Tensions and ambivalences are exposed as the participants both adopted and resisted elements of ‘girly’ and ‘tomboy’ identities. I then explore the ways in which forms of classed othering function to construct the feminine self in contrast to those who are perceived to lack the taste and resources to ‘do’ femininity appropriately and instead embody a somehow inauthentic and overdone performance of femininity. I briefly consider the intersections between hyper-feminine and ‘slutty’ dress, and finally explore how attempts by working-class young women to resignify a more excessive look as ‘glamorous’ may be mocked and judged beyond the local context.
Keywords: Essex Girl; Geordie; Girly Girl; Tomboy; clothingClothing

Men's Intrusion, Women's Embodiment: A critical analysis of street harassment - Vera-Gray, F. (Routledge, 2018)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.

“The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Bennett, Toby (IASPM Journal, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.
Keywords: Industrial Reflexivity; Inequalities; KEYWORDS: Creative labour; Major record labels; Post-feminism.

'Shocking' level of sexual harassment at music festivals (BBC News, 2018)
Up to 43% of women under 40, who have been to a music festival, say they have faced unwanted sexual behaviour.

The music business’s gender pay gap is embarrassing and uncomfortable. It’s time for change. (Music Business Worldwide, 2018)
MBW Contributing Editor, Rhian Jones, gives her take on the news…

EDM and Ecstasy: the lived experiences of electronic dance music festival attendees - Little, Noah; Burger, Birgitta; Croucher, Stephen M. (Journal of New Music Research, 2018)
Attendance at large-scale music festivals has captivated a global interest in these spectacular experiences, yet little is known about the lasting benefits and personal changes individuals incur following this event. This study aims to provide a comprehensive exploration of the lived experiences of individuals who attended a multi-day electronic dance music festival. The present study was primarily interested in the perceived beneficial changes within the individual, following their festival experience. We investigated if first-time festival attendees perceived changes differed to those of returning individuals. Semi-structured qualitative interviews were used to collect data from 12 individuals who attended the 2015 Electronic Daisy Carnival in Las Vegas. Six participants were first-time attendees while the remaining six were individuals returning to the festival. The data was analysed using Thematic Analysis. Within the data emerged the following central themes: (1) escape, (2) communitas, and (3) self-reported changes; there were 10 subthemes. These findings add to the existing body of music festival literature, further contextualizing how music festivals are both experienced, and reflected upon by individuals. Further, this study highlights the potential lasting changes individuals’ experience from attending electronic dance music festivals.
Keywords: Music festival; electronic dance music; music; social acceptance; social cohesion

“Essential—Passion for Music”: Affirming, Critiquing, and Practising Passionate Work in Creative Industries - Bennett, Toby (The Palgrave Handbook of Creativity at Work, 2018)
This chapter considers “passion” as an enthusiastic orientation to work within creative worlds: work motivated by intense attachments to the products of work and their conditions of production. Drawing on Luc Boltanski’s pragmatic sociology of critique and justification, the chapter argues that the passionate lens most usefully trains our sights on normative questions: not what or how—but why such work is undertaken. Embedded in research on cultural and creative industries, the contemporary recorded music sector is presented as a “passionate” industry in transformation. Interviews with workers, who both criticize and defend their industry, act as a springboard to explore three possible interpretive approaches: affirmative, critical, and pragmatic. Theoretical flexibility is needed to keep “passion” open to future inquiry—particularly regarding inequalities in creative work.

"I Didn't Want To Be 'That Girl'": The Social Risks of Labeling, Telling, and Reporting Sexual Assault - Khan, Shamus; Hirsch, Jennifer; Wamboldt, Alexander; Mellins, Claude (Sociological Science, 2018)
This article deploys ethnographic data to explain why some students do not label experiences as sexual assault or report those experiences. Using ideas of social risks and productive ambiguities, it argues that not labeling or reporting assault can help students (1) sustain their current identities and allow for several future ones, (2) retain their social relationships and group afﬁliations while maintaining the possibility of developing a wider range of future ones, or (3) avoid derailing their current or future goals within the higher educational setting, or what we call “college projects.” Conceptually, this work advances two areas of sociological research. First, it expands the framework of social risks, or culturally speciﬁc rationales for seemingly illogical behavior, by highlighting the interpersonal and institutional dimensions of such risks. Second, it urges researchers to be more attentive to contexts in which categorical ambiguity or denial is socially productive and to take categorical avoidance seriously as a subject of inquiry. Substantively, this work advances knowledge of why underreporting of campus sexual assault occurs, with implications for institutional policies to support students who have experienced unwanted nonconsensual sex regardless of how those students may label what happened.

Navigating the Margins between Consent and Dissent: Mechanisms of Creative Control and Rock Music in Late Socialist Romania - Mogoș, Petrică; Berkers, Pauwke (East European Politics and Societies: and Cultures, 2018)

The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Toby, Bennett (Gender Politics in the Music Industry, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.

Gender in the Music Industry: Rock, Discourse and Girl Power - Leonard, Marion (Routledge, 2017)
Why, despite the number of high profile female rock musicians, does rock continue to be understood as masculine? Why is rock generally assumed to be created and performed by men? Marion Leonard explores different representations of masculinity offered by, and performed through, rock music, and examines how female rock performers negotiate this gendering of rock as masculine. A major concern of the book is not specifically with men or with women performing rock, but with how notions of gender affect the everyday experiences of all rock musicians within the context of the music industry. Leonard addresses core issues relating to gender, rock and the music industry through a case study of 'female-centred' bands from the UK and US performing so called 'indie rock' from the 1990s to the present day. Using original interview material with both amateur and internationally renowned musicians, the book further addresses the fact that the voices of musicians have often been absent from music industry studies. Leonard's central aim is to progress from feminist scholarship that has documented and explored the experience of female musicians, to presenting an analytic discussion of gender and the music industry. In this way, the book engages directly with a number of under-researched areas: the impact of gender on the everyday life of performing musicians; gendered attitudes in music journalism, promotion and production; the responses and strategies developed by female performers; the feminist network riot grrrl and the succession of international festivals it inspired under the name of Ladyfest.

Rape and abuse: The music industry's dark side exposed (BBC News, 2017)
"Dangerous men" at the top of the industry are abusing their power, the BBC has been told.

2192 women in the Swedish music industry behind appeal against sexism (Dagens Nyheter, 2017)
Sexual assault. Rude and outspoken sexism.

Forty-Seven DJs, Four Women: Meritocracy, Talent, and Postfeminist Politics - Gadir, Tami (Dancecult, 2017)
In 2016, only four of forty-seven DJs booked for Musikkfest, a festival in Oslo, Norway, were women. Following this, a local DJ published an objection to this imbalance in a local arts and entertainment magazine. Her editorial provoked booking agents to defend their position on the grounds that they prioritise skill and talent when booking DJs, and by implication, that they do not prioritise equality. The booking agents’ responses, on social media and in interviews I conducted, highlight their perpetuation of a status quo in dance music cultures where men disproportionately dominate the role of DJing. Labour laws do not align with this cultural attitude: gender equality legislation in Norway’s recent history contrasts the postfeminist attitudes expressed by dance music’s cultural intermediaries such as DJs and booking agents. The Musikkfest case ultimately shows that gender politics in dance music cultures do not necessarily correspond to dance music’s historical associations with egalitarianism.

Justice 2.0: Street harassment victims’ use of social media and online activism as sites of informal justice - Fileborn, Bianca (The British Journal of Criminology, 2017)
Emerging scholarship has considered the potential for online spaces to function as sites of informal justice. To date, there has been little consideration of the experiences of individuals who seek justice online, and the extent to which victims’ justice needs can be met online. Drawing on the findings of a mixed-methods research project with street harassment victims in Melbourne, Australia, I consider participants’ reasons for, and experiences of, disclosing their encounters of street harassment online. I examine the extent to which these ‘map on to’ a selection of victim’s justice needs. While it is evident that online spaces can function as sites of justice, it is vital to ask for whom and in which contexts justice can be achieved online.

Gender, Subjectivity, and Cultural Work: The Classical Music Profession - Scharff, Christina (Routledge, 2017)
What is it like to work as a classical musician today? How can we explain ongoing gender, racial, and class inequalities in the classical music profession? What happens when musicians become entrepreneurial and think of themselves as a product that needs to be sold and marketed? Gender, Subjectivity, and Cultural Work explores these and other questions by drawing on innovative, empirical research on the working lives of classical musicians in Germany and the UK. Indeed, Scharff examines a range of timely issues such as the gender, racial, and class inequalities that characterise the cultural and creative industries; the ways in which entrepreneurialism – as an ethos to work on and improve the self – is lived out; and the subjective experiences of precarious work in so-called ‘creative cities’. Thus, this book not only adds to our understanding of the working lives of artists and creatives, but also makes broader contributions by exploring how precarity, neoliberalism, and inequalities shape subjective experiences. Contributing to a range of contemporary debates around cultural work, Gender, Subjectivity, and Cultural Work will be of interest to scholars and students in the fields of Sociology, Gender and Cultural Studies.
Keywords: Music; Myriam; Social Science / General; Social Science / Sociology / General

Architects singer calls out man who sexually assaulted a fan: 'Not at my f***ing show' (The Independent, 2017)
Singer paused the show after witnessing the incident from the stage

Swedish music festival to go 'women-only' following string of sexual assaults - White, Adam (The Telegraph, 2017)
Sweden's biggest music festival will be replaced next year by a women-only alternative after reports of a series of rapes and sexual assaults at this year's event.
Keywords: Crime; Culture; Music; Skepta; Standard; Sweden

Data and responsibility: Towards a feminist methodology for producing historical data on women in the contemporary UK film industry - Cobb, Shelley; Wreyford, Natalie (Feminist Media Histories, 2017)
This paper addresses how feminist interrogations of research methods and knowledge claims have an important role to play in the collection and dispersion of quantitative data. Taking the contemporary film industry as a historical formation, and seeking to identify and understand patterns of continued gendered inequality, we consider the methodological and ethical dilemmas we have experienced as feminist researchers gathering and presenting quantitative data on the numbers of women working in the UK film industry between 2003 and 2015. We argue that data plays a paradoxical role in creating a sense of women’s absence and arrive at a set of guiding principles for feminist quantitative research in film histories.

The deterrent effects of Australian street-level drug law enforcement on illicit drug offending at outdoor music festivals - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne; Ritter, Alison; Weatherburn, Don; MacCoun, Robert (International Journal of Drug Policy, 2017)
Background Australian and international street-level drug law enforcement deploy many strategies in efforts to prevent or deter illicit drug offending. Limited evidence of deterrence exists. This study assessed the likely impacts of four Australian policing strategies on the incidence and nature of drug use and supply at a common policing target: outdoor music festivals. Methods A purpose-built national online survey (the Drug Policing Survey) was constructed using five hypothetical experimental vignettes that took into account four policing strategies (High Visibility Policing, Riot Policing, Collaborative Policing, and policing with Drug Detection Dogs) and a counter-factual (no police presence). The survey was administered in late 2015 to 2115 people who regularly attend festivals. Participants were block-randomised to receive two vignettes and asked under each whether they would use, possess, purchase, give or sell illicit drugs. Results Compared to ‘no police presence’, any police presence led to a 4.6% point reduction in engagement in overall illicit drug offending: reducing in particular willingness to possess or carry drugs into a festival. However, it had minimal or counterproductive impacts on purchasing and supply. For example, given police presence, purchasing of drugs increased significantly within festival grounds. Offending impacts varied between the four policing strategies: Drug Detection Dogs most reduced drug possession but High Visibility Policing most reduced overall drug offending including supply. Multivariate logistic regression showed police presence was not the most significant predictor of offending decisions at festivals. ConclusionConclusion The findings suggest that street-level policing may deter some forms of drug offending at music festivals, but that most impacts will be small. Moreover, it may encourage some perverse impacts such as drug consumers opting to buy drugs within festival grounds rather than carry in their own. We use our findings to highlight trade-offs between the goals of public health promotion and crime control in street-level enforcement.
Keywords: Deterrence; Drug law enforcement; Supply; Use

Rape culture, lad culture and everyday sexism: researching, conceptualizing and politicizing new mediations of gender and sexual violence - Phipps, Alison; Ringrose, Jessica; Renold, Emma; Jackson, Carolyn (Journal of Gender Studies, 2017)
Introduction to Special Issue of Journal of Gender Studies entitled Rape culture, lad culture and everyday sexism: Researching, conceptualizing and politicizing new mediations of gender and sexual violence.

Skipping a beat: Assessing the state of gender equality in the Australian music industry - Cooper, Rae; Coles, Amanda; Hanna-Osborne, Sally (2017)
This report demonstrates that male advantage is a pervasive feature of the Australian music industry. Using publicly available published data the report interrogates the industry dynamics that have produced a contemporary music scene in which radio playlists, festival line-ups, industry awards, peak bodies and major industry boards are dominated by male contributions and voices. We make 5 key recommendations, discussed in more detail in the report, to begin the process of addressing the industry’s chronic gender inequality: 1. Collect more and better data on the music industry on a gender disaggregated basis; 2. Establish a well-resourced independent gender equality industry advocacy body; 3. Use gender equality criteria in deciding public funding outcomes; 4. Increase women’s representation in decision-making structures; 5. Address gender bias in the Australian music industry by prioritising inclusivity and representation as core industry values (for example through funding and implementing training programs). The music industry is skipping a beat when it comes to gender equality. We hope that our report will stimulate industry thinking and action for change.

The Going Out In Sydney App: Evaluating the Utility of a Smartphone App for Monitoring Real-World Illicit Drug Use and Police Encounters Among Festival and Club Goers - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne Louisa (Substance Abuse: Research and Treatment, 2017)
Gaining accurate information on illicit drug use and policing in real-world settings is a challenge. This study examines the utility of a smartphone app (‘Going Out In Sydney’) to prospectively follow up illicit drug use and policing encounters at music festivals and licensed entertainment precincts in Sydney, Australia. In all, 38 regular festival and licensed entertainment venue attendees used the app to log nights out over a 3-month period, including (1) where they went (eg, festival, nightclub), (2) the prevalence of illicit drug use, and (3) the incidence and nature of police encounters. A survey and interview were then conducted about the utility of the app. The app enabled rich data collection (n = 353 entries) about illicit drug use and policing at both target settings. Follow-up surveys indicated that most participants were extremely satisfied with the ease of use of the app and privacy afforded, and compared with other data collection modes, such as paper-based logs and online surveys, rated the app the most desirable method of data collection. This suggests smartphone apps may be a viable option for future studies on illicit drug use and policing of drugs.
Keywords: Mobile app; app; drug use; offending; policing; smartphone

gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, S (International Journal of Cultural Policy, 2017)

Our Music My Body: 2017 Campaign & Survey Report - OurMusicMyBody (2017)
Keywords: Bibliographie; Nettoyer

Brit awards announce voting shakeup after #BritsSoWhite outrage (the Guardian, 2016)
Organisers say academy is more gender-balanced and diverse after last year’s failure to nominate black artists

How to be a boss woman in the music industry - Jones, Rhian (Medium, 2016)
The music industry is hugely homogenised. In the UK, all three heads of the major record labels are men, and there’s just three women…

Drugs at the campsite: Socio-spatial relations and drug use at music festivals - Dilkes-Frayne, Ella (International Journal of Drug Policy, 2016)
Background Music festivals have received relatively little research attention despite being key sites for alcohol and drug use among young people internationally. Research into music festivals and the social contexts of drug use more generally, has tended to focus on social and cultural processes without sufficient regard for the mediating role of space and spatial processes. Methods Adopting a relational approach to space and the social, from Actor-Network Theory and human geography, I examine how socio-spatial relations are generated in campsites at multiple-day music festivals. The data are drawn from ethnographic observations at music festivals around Melbourne, Australia; interviews with 18–23 year olds; and participant-written diaries. Results Through the analysis, the campsite is revealed as a space in process, the making of which is bound up in how drug use unfolds. Campsite relations mediate the formation of drug knowledge and norms, informal harm reduction practices, access to and exchange of drugs, and rest and recovery following drug use. Conclusions Greater attendance to socio-spatial relations affords new insights regarding how festival spaces and their social effects are generated, and how they give rise to particular drug use practices. These findings also point to how festival harm reduction strategies might be enhanced through the promotion of enabling socio-spatial relations.
Keywords: Drug use; Enabling places; Ethnography, Music festivals; Social context; Socio-spatial relations

Nightlife Ethnography, Violence, Policing and Security - Tomsen, Stephen; Wadds, Phillip (2016)

Post-postfeminism? New feminist visibilities in postfeminist times - Gill, R. (Feminist Media Studies, 2016)
This article contributes to debates about the value and utility of the notion of postfeminism for a seemingly “new” moment marked by a resurgence of interest in feminism in the media and among young women. The paper reviews current understandings of postfeminism and criticisms of the term’s failure to speak to or connect with contemporary feminism. It offers a defence of the continued importance of a critical notion of postfeminism, used as an analytical category to capture a distinctive contradictory-but-patterned sensibility intimately connected to neoliberalism. The paper raises questions about the meaning of the apparent new visibility of feminism and highlights the multiplicity of different feminisms currently circulating in mainstream media culture – which exist in tension with each other. I argue for the importance of being able to “think together” the rise of popular feminism alongside and in tandem with intensified misogyny. I further show how a postfeminist sensibility informs even those media productions that ostensibly celebrate the new feminism. Ultimately, the paper argues that claims that we have moved “beyond” postfeminism are (sadly) premature, and the notion still has much to offer feminist cultural critics.

Cultural value and cultural policy: some evidence from the world of live music - Behr, Adam; Brennan, Matt; Cloonan, Martin (International Journal of Cultural Policy, 2016)
This article considers live music policy in relation to wider debates on the cultural (as opposed to instrumental) value of the arts. The findings are based on research into amateur/enthusiast, state-funded and commercial concerts across a range of genres – classical, traditional folk, jazz, singer–songwriter and indie – using the Edinburgh Queen’s Hall venue as a case study. We argue that (1) articulations of the cultural or intrinsic value of live music across genres tend to lapse back into descriptions of instrumental value; (2) although explanations vary from audiences, artists and promoters as to why they participate in live music, they also share certain characteristics across genres and sometimes challenge stereotypes about genre-specific behaviours; and (3) there are lessons to be learned for live music policy from examining a venue that plays host to a range of genres and promotional practices.
Keywords: audience research; cultural value; live music; music policy; regulation

How can the music industry tackle its diversity issues? (Music Business Worldwide, 2016)
Kieron Faller from CI reveals best-practice for diverse businesses…

Taking time between g-string changes to educate ourselves: Sinéad O’Connor, Miley Cyrus, and celebrity feminism - Brady, Anita (Feminist Media Studies, 2016)
This article examines the feminist response to a 2013 online “feud” between singers Miley Cyrus and Sinéad O’Connor that began when Cyrus connected the video for her single “Wrecking Ball” to O’Connor’s video for “Nothing Compares 2 U.” O’Connor’s response criticised Cyrus’ sexualised image, and the exchanges that followed sparked debate among feminists over the limits of sexual “agency,” and the sexual politics of feminism. This took place within a wider media context that has seen an apparent increase in female celebrities explicitly identifying themselves as feminist. Critics of this “celebrity feminism” argue that the sexualised star systems of its proponents are at odds with the aims of feminist politics. This article draws on post-structuralist feminist theory to question the positioning of celebrity feminism as exterior to an imagined “feminist movement.” Using the Cyrus/O’Connor feud, I argue that such a binary potentially reaffirms the structures of power that feminism seeks to oppose, and ignores the ways celebrity culture and contemporary media practice might combine to produce new understandings of the field of feminism.
Keywords: Celebrity feminism; Miley Cyrus; Sinéad O’Connor; feminist post-structuralism; third-wave feminism

Risky Pleasures?: Club Cultures and Feminine Identities - Hutton, Fiona (Routledge, 2016)
In this book Fiona Hutton provides a fascinating insight into women's experiences of clubbing. Based on a rich ethnographic account of the Manchester club scene, Risky Pleasures? is set within the context of the theoretical literature on youth subcultures, female friendship, consumption, risk and the city. The work highlights both the producers of club scenes - promoters, DJs, dealers - and the consumers - women negotiating pleasure and risk in club spaces and in the city at night. It explores the range of club spaces, developing a typology of 'mainstream' and 'underground' clubs, and considers how different types of participants are attracted to different 'scenes'. It examines women's recreational drug-use within a club context and discusses issues of sexuality, tolerance and the importance of 'attitude' in terms of women's feelings of safety. Revealing the important role of different spaces and different atmospheres in how women participate in club scenes, Fiona Hutton argues that drug taking and sexual pleasure are always contextualized within the environments created in different spaces, and that the risk and danger negotiated by women clubbers are counterbalanced by fun and pleasure - and ultimately empowerment.

Challenging the Myth of Gender Equality in Sweden - Lena, Martinsson; Gabriele, Griffin (Policy Press, 2016)
Sweden is often considered one of the most gender-equal countries in the world and held up as a model to follow, but the reality is more complex. This is the first book to explode the myth of Swedish gender equality, both offering a new perspective for an international audience, and suggesting how equality might be rethought more generally. While the authors argue that the gender-equality mantra in Sweden has led to a society with increased opportunities for some, they also assert that the dominant norm of gender equality has become nationalistic and builds upon heteronormative and racial principles. Examining the changing meanings and parameters of gender equality against the country's social-democratic tradition and in the light of contemporary neoliberal ideologies, the book constitutes an urgent contribution to the debates about gender-equality policies and politics.
Keywords: Social Science / Gender Studies; Social Science / Sociology / General

Valuing Musical Participation - Pitts, Stephanie (Routledge, 2016)
Increasingly, it is becoming evident that those involved in socio-musical studies must focus their investigative lens on musical practice and articulation of the self, on music and community involvement and on music as a social medium for social relationships. What motivates people to be involved in musical performance, and how do they articulate these needs and drives? What do performers gain from their involvement in musical activities? How do audience members perceive their relationship to the performer, the music and the event? These questions and many more are addressed here with the benefit of detailed empirical work, including case studies of a chamber music festival and a contemporary music summer school. Pitts investigates the value of musical participation for performers and audience members in a range of contexts, using a multi-disciplinary approach to place new empirical data in the framework of existing theory and literature. Themes examined include: the shared musical experience; the social structures of performing societies; how people identify with music; the values implicit in musical preferences; the social responsibilities of the performer; the audience view of concerts and festivals; the social power of music and educational implications and responsibilities. Pitts draws upon literature from musicology, sociology and psychology of music, ethnomusicology, music education and community music to demonstrate the diversity of enquiry about musical behaviours. The conclusions of the book are based upon empirical evidence gleaned through case studies, with the data integrated thematically throughout, to enable a greater depth of discussion than individual studies usually permit.

Who are the most powerful people in music? Jay Z? Kanye? Beyoncé? No, it’s old white men (the Guardian, 2016)
The 2016 Billboard Power 100 is dominated by white men born before Elvis had a hit. This isn’t only a problem of representation – it’s also bad for the industry

Learning to labour unequally: Understanding the relationship between cultural production, cultural consumption and inequality - Oakley, Kate; O'Brien, Dave (Social Identities, 2016)
Inequality has become essential to understanding contemporary society and is at the forefront of media, political and practice discussions of the future of the arts, particularly in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The article considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The paper argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy, despite the importance of culture to British and thus international policy agendas. The article uses the example of higher education in the UK to think through the relationship between cultural consumption and production. In doing, so the article maps out a productive possibility for a new research agenda, by sketching where and how research might link cultural consumption and production to better understand inequality.

Gender, Metal and the Media: An Introduction - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill offers a much needed discussion of the lack of consideration given to gender in academic discussions of hard rock and metal music and the media. Drawing on her own experience as a musician and fan, the author argues that orthodoxies—e.g., the genre is inclusive, the music asexual and sexism non-existent—are only able to persist within the literature because scholars have neglected to understand how musical experiences are gendered. Within the context of feminist popular music scholarship, work on fandom and feminist methodological work, Hill outlines the need to study hard rock, metal and the media with close attention to the influence of gender.
Keywords: Black Metal; Hard Rock; Metal Music; Rock Music; Social Expression

Hard Rock and Metal as an Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill examines the differing theoretical frameworks, e.g., subculture and scene, used to examine hard rock and metal fans, arguing that these have worked to the detriment of understanding the gendered experience of music, including taking pleasure in the music. She proposes a new way of thinking about fandom that incorporates fans’ feelings of community. Drawing on Anderson’s (Imagined Communities: Reflections on the Origin and Spread of Nationalism. Verso, 1991) theory of the nation, and feminist writings on community (Weiss and Friedman, Feminism and Community. Temple University Press, 1995), she argues that ‘imaginary community’ better reflects fans’ sense of community, whilst allowing deep consideration of the ideology of the community with particular reference to values, beliefs, traditions and myths. She argues that these are deployed to create a sense of cohesion in spite of inequalities and unacknowledged privileges.
Keywords: Extreme Metal; Gender Construction; Hard Rock; Metal Community; Moral Panic

Listening to Hard Rock and Metal Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter challenges readings of hard rock and metal as masculine music. Hill examines women’s accounts of their experiences of musical pleasure. Through analysis of women fans’ descriptions of their favourite bands, she argues that, pace Kahn-Harris (2007), fans can be very articulate about what they like. Work of feminist writers on rock music is enlisted to argue that considering women’s listening pleasure gives new insights into the meaning of hard rock and metal music. The assumption that hard rock and metal is a masculine genre neglects important aspects of women’s fandom which diverge from the dominant myths.
Keywords: False Consciousness; Hard Rock; Heavy Metal; Musical Experience; Rock Music

Metal and Sexism - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 6 considers the allegations that hard rock and metal is sexist. Talking to British women fans reveals that in their experiences, hard rock and metal is less sexist than the ‘mainstream’. Using research on sexism across a range of fields, Hill argues that understanding what counts as sexism is complex and requires critical work by fans when sexism is normalised. Listening to what fans say about the context of their experiences within their broader lives is vital for better understanding. The author argues that the genre provides moments in which women fans may gain a feeling of genderlessness. Ultimately, however, the feeling of liberation only comes through assimilation into the culture, a culture that ignores women as much as possible. Nevertheless, that temporary feeling is a valuable one.
Keywords: Hard Rock; Metal Event; Music Video; Sexual Harassment; Unwanted Sexual Attention

The Gendered Experience of Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
The final chapter argues that close examination of the specific experiences of women in their engagements with the hard rock and metal media, the music, and musical events reveals how the experience of music is shaped by sexist assumptions about women and about how music should be listened to. Musical pleasure does not exist on a universal, transcendental plane. It is informed and shaped by the socio-cultural circumstances of the listener. Hill maintains that it is vital to acknowledge how these circumstances make for differing experiences: it is an important first step for countering sexism. The chapter concludes with a short plan for how hard rock and metal may imagine a genderless future, and how this imagined community might work towards it.
Keywords: Hard Rock; Metal Musician; Music Culture; Normative Femininity; Science Fiction

The Media and the Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter investigates how Kerrang! magazine, a key part of the metal media, creates an imaginary community of hard rock and metal fans. Using semiotic analysis, the author extrapolates four myths that are forged in the letters pages: two that are presented by the magazine as being common sense values of the community (equality and authenticity) and two that are less obvious, the groupie and the warrior, which determine how women and men are portrayed. These myths work together to depict the imaginary community as ideologically invested in maintaining the masculinity of the genre at the expense of femininity. Hill argues that dominant representations of women in the imaginary community render them as adjuncts to the real members of the community—the men—and this has damaging consequences.
Keywords: Hard Rock; Hegemonic Masculinity; Horror Film; Letter Writer; Metal Community

Women Fans and the Myth of the Groupie - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 4 scrutinises the impact that the myth that women fans are groupies has on British hard rock and metal women fans. Women fans must negotiate the stereotype without accepting the title if they want their fandom to be respected, this results in a defensiveness about sexual and fannish reputations, which is an overtly gendered experience. Hill moves to examine the ways in which women’s desire for musicians and the complicated ways in which it must be negotiated impact on fans’ ability to express their fandom and their sexuality. The problem of the groupie myth lies not just with the expectations it places upon women but also in the ways in which it prevents discussion of more sensual and embodied experiences of musical pleasure.
Keywords: Hard Rock; Music Industry; Physical Attraction; Sexual Attraction; Sexual Pleasure

‘Safe Spaces’: Experiences of Feminist Women-Only Space - Lewis, Ruth; Sharp, Elizabeth; Remnant, Jenni; Redpath, Rhiannon (Sociological Research Online, 2015)
The gendered nature of safety has been explored empirically and theoretically as awareness has grown of the pervasive challenges to women's safety. Notions of ‘safe space’ are frequently invoked in wider feminist environments (particularly, recently, in relation to debates about trans people's access to women's spaces), but are relatively neglected in academia. Indeed, despite a body of scholarship which looks at questions of gender, safety and space, relatively little attention has been paid to exploring the meaning of ‘safety’ for women and, particularly, the meaning and experience of spaces they consider to be ‘safe.’ Drawing on focus group data with 30 women who attended a two-day, women-only feminist gathering in the UK, this paper analyses experiences of what they describe as ‘safe space’ to explore the significance and meaning of ‘safety’ in their lives. Using their accounts, we distinguish between safe from and safe to, demonstrating that once women are safe from harassment, abuse and misogyny, they feel safe to be cognitively, intellectually and emotionally expressive. We argue that this sense of being ‘safe to’ denotes fundamental aspects of civic engagement, personhood and freedom.
Keywords: Activism; Feminism; Safety; Space; Women; Women-Only

Victoria Sets Up Taskforce To Tackle Harassment Of Women At Gigs (Tone Deaf, 2015)
Following a meeting of the Victorian Live Music Roundtable yesterday, Victorian Minister for Consumer Affairs, Gaming and Liquor Regulation Jane Garrett

All the girls in town: The missing women of Australian rock, cultural memory and coverage of the death of Chrissy Amphlett - Strong, Catherine (Perfect Beat, 2015)
This article will use the cultural and media materials produced around the death of Chrissy Amphlett as a way of interrogating the fact that surprisingly few resources exist that document or commemorate the contribution of women to the rock music scene in Australia. As Amphlett is unusual in being a woman who has, even before her death, claimed a place in the Australian rock canon, examining materials that are designed to construct her legacy upon her passing will provide examples of how women in Australian rock are discussed. It will be demonstrated that Amphlett’s gender is central to these discussions, and that she is used to both obscure the contributions of other women performers and to deny a need for women musicians to even be an object of discussion at all. These indings will be analysed using Aleida Assmann’s concepts of functional and storage memory, and it will be argued that the lack of information that we have about past female rockers makes it harder for women in Australia to see this ield as one they can participate in, and also makes the retention of memories about currently successful women musicians less likely.

Pathways to Help: Adolescent Sexual Assault Victims’ Disclosure and Help-Seeking Experiences - Campbell, Rebecca; Greeson, Megan R.; Fehler-Cabral, Giannina; Kennedy, Angie C. (Violence Against Women, 2015)
In this study, we conducted semistructured interviews with N = 20 adolescent sexual assault victims who sought postassault help from the medical and legal system to understand young survivors’ disclosure and help-seeking processes. Results revealed three distinct disclosure patterns and pathways to help-seeking. First, in the voluntary disclosure group, victims told their friends, who encouraged them to tell an adult, who then encouraged—and assisted—the survivors in seeking help. Throughout this process, the survivors’ disclosures at each step were within their control and reflected their choices for how to proceed. Second, in the involuntary disclosure pattern, victims also first disclosed to friends, but then those friends told adults about the assault, against the survivors’ wishes; the adults made the victims seek help, which was also against the survivors’ preferences. Third, in situational disclosures, the survivors were unconscious at the time of the assault, and their friends disclosed and sought help on their behalf. We also examined how these initial disclosure patterns related to victims’ continued engagement with these systems.
Keywords: adolescents; disclosure; help-seeking; rape; sexual assault

Cultural Value and Inequality: A Critical Literature Review - Oakley, K; O'Brien, D (2015)
Inequality has become essential to understanding contemporary British society and is at the forefront of media, political and practice discussions of the future of the arts in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The literature review considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The review argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy. The review concentrates on the ‘big three’ issues of inequality – race, class and gender, where most of the literature is to be found, but also touches on disability, sexuality and spatial inequality. All of the research reviewed suggests an undeniable connection between cultural value and inequality. Understanding that connection is currently impeded by problems with data. The report suggests the political saliency of this topic means that public policy must do more to provide robust research, particularly about cultural production.

Sex, Gender and Work Segregation in the Cultural Industries - Hesmondhalgh, David; Baker, Sarah (The Sociological Review, 2015)
This chapter addresses work ‘segregation’ by sex in the cultural industries. We outline some of the main forms this takes, according to our observations: the high presence of women in marketing and public relations roles; the high numbers of women in production co-ordination and similar roles; the domination of men of more prestigious creative roles; and the domination by men of technical jobs. We then turn to explanation: what gender dynamics drive such patterns of work segregation according to sex? Drawing on interviews, we claim that the following stereotypes or prevailing discourses, concerning the distinctive attributes of women and men, may influence such segregation: that women are more caring, supportive and nurturing; that women are better communicators; that women are ‘better organized’; and that men are more creative because they are less bound by rules.
Keywords: cultural industries; sexual division of labour; stereotypes; work segregation

Resilience & Melancholy: Pop Music, Feminism, Neoliberalism - James, Robin (John Hunt Publishing, 2015)
When most people think that “little girls should be seen and not heard,” a noisy, riotous scream can be revolutionary. But that’s not the case anymore. (Cis/Het/White) Girls aren’t supposed to be virginal, passive objects, but Poly-Styrene-like sirens who scream back in spectacularly noisy and transgressive ways as they “Lean In.” Resilience is the new, neoliberal feminine ideal: real women overcome all the objectification and silencing that impeded their foremothers. Resilience discourse incites noisy damage, like screams, so that it can be recycled for a profit. It turns the crises posed by avant-garde noise, feminist critique, and black aesthetics into opportunities for strengthening the vitality of multi-racial white supremacist patriarchy (MRWaSP). Reading contemporary pop music – Lady Gaga, Beyonce, Calvin Harris – with and against political philosophers like Michel Foucault, feminists like Patricia Hill Collins, and media theorists like Steven Shaviro, /Resilience & Melancholy/ shows how resilience discourse manifests in both pop music and in feminist politics. In particular, it argues that resilient femininity is a post-feminist strategy for producing post-race white supremacy. Resilience discourse allows women to “Lean In” to MRWaSP privilege because their overcoming and leaning-in actively produce blackness as exception, as pathology, as death. The book also considers alternatives to resilience found in the work of Beyonce, Rihanna, and Atari Teenage Riot. Updating Freud, James calls these pathological, diseased iterations of resilience “melancholy.” Melancholy makes resilience unprofitable, that is, incapable of generating enough surplus value to keep MRWaSP capitalism healthy. Investing in the things that resilience discourse renders exceptional, melancholic siren songs like Rihanna’s “Diamonds” steer us off course, away from resilient “life” and into the death.
Keywords: Bibliographie; Music / History & Criticism; Nettoyer; Philosophy / Social

The Economic and Cultural Value of Live Music in Australia 2014 - Carter, D. (2015)
The Economic and Cultural Value of Live Music in Australia 2014

Gender and creative labour - Conor, B; Gill, R; Taylor S (The Sociological Review, 2015)
Keywords: gender inequality; neoliberalism; precariousness; self-representation; sexism

Unspeakable Inequalities: Post Feminism, Entrepreneurial Subjectivity, and the Repudiation of Sexism among Cultural Workers - Gill, Rosalind (Social Politics: International Studies in Gender, State & Society, 2014)
Work in the cultural and creative fields is marked by stark and growing inequalities relating to gender, class, and race/ethnicity. Yet, the same industries are also characterised by an ethos that celebrates openness, egalitarianism, and meritocracy. This paper explores this paradox, focusing in particular on gender inequalities. It argues that there is a need to move beyond the standard conventional explanations for women's under-representation within the creative workforce, which point to female childbearing and childcare as central. Whilst not disputing the significance of motherhood to women's career trajectories, the paper suggests that the repeated focus on maternity is problematic and may close down other areas of potential investigation and critique. The paper suggests that three alternative foci would repay attention in understanding inequalities in the CCI. First, the new, mobile, subtle, and revitalised forms of sexism in circulation urgently require further examination. Secondly, the power of the dominant post feminist sensibility which, in suggesting that “all the battles have been won,” renders inequality increasingly difficult to voice or speak about, demands critique. Thirdly, the new forms of labouring subjectivity required to survive in the field of cultural work may themselves be contributing to the inequalities in the field, by favouring an entrepreneurial individualistic mode that disavows structural power relations. These three aspects of life in the field of cultural work merit further attention and suggest that gender inequality has a variety of different causes, not all located in women's childbearing abilities. Moreover, the paper argues that the very myth of egalitarianism at work in the CCI may itself be a key mechanism through which inequality is reproduced.

“Blurred Lines?” Sexual Aggression and Barroom Culture - Graham, Kathryn; Bernards, Sharon; Osgood, D. Wayne; Abbey, Antonia; Parks, Michael; Flynn, Andrea; Dumas, Tara; Wells, Samantha (Alcoholism, clinical and experimental research, 2014)
Background Meeting potential sexual/romantic partners for mutual pleasure is one of the main reasons young adults go to bars. However, not all sexual contacts are positive and consensual, and aggression related to sexual advances is a common experience. Sometimes such aggression is related to misperceptions in making and receiving sexual advances while other times aggression reflects intentional harassment or other sexually aggressive acts. The present study uses objective observational research to assess quantitatively gender of initiators and targets and the extent that sexual aggression involves intentional aggression by the initiator, the nature of responses by targets, and the role of third parties and intoxication. Methods We analyzed 258 aggressive incidents involving sexual advances observed as part of a larger study on aggression in large capacity bars and clubs, using variables collected as part of the original research (gender, intoxication, intent) and variables coded from narrative descriptions (invasiveness, persistence, targets’ responses, role of third parties). Hierarchical Linear Modeling (HLM) analyses were used to account for nesting on incidents in evening and bars. Results 90% of incidents involved male initiators and female targets, with almost all incidents involving intentional or probably intentional aggression. Targets mostly responded nonaggressively, usually using evasion to end the incident. Staff rarely intervened; patron third parties intervened in 21% of incidents, usually to help the target but sometimes to encourage the initiator. Initiators’ level of invasiveness was related to intoxication of the targets but not their own intoxication, suggesting intoxicated women were being targeted. Conclusions Sexual aggression is a major problem in bars often reflecting intentional sexual invasiveness and unwanted persistence rather than misperceptions in sexual advances. Prevention needs to focus on addressing masculinity norms of male patrons and staff that support sexual aggression and better management of the highly sexualized and sexist environments of most bars.
Keywords: Camille

Fortunes of feminism: from state-managed capitalism to neoliberal crisis - Guest, Carly (European Journal of Cultural and Political Sociology, 2014)

Safe Space: Towards a Reconceptualization (Antipode, 2014)
The term “safe space” dates to the late twentieth century women's movement, but it has since been used in many different contexts. In this paper, we review and analyze historical and contemporary “safe spaces”. These include “separatist” safe spaces in women's, anti-racist, and feminist communities, “inclusive” safe space classrooms, and safe spaces in which (non-human) objects are central. We argue that safe spaces should be understood not through static and acontextual notions of “safe” or “unsafe”, but rather through the relational work of cultivating them. Such an understanding reveals several tendencies. Namely, safe spaces are inherently paradoxical. Cultivating them includes foregrounding social differences and binaries (safe–unsafe, inclusive–exclusive) as well as recognizing the porosity of such binaries. Renegotiating these binaries is necessarily incomplete; a safe space is never completely safe. Even so, we encourage the critical cultivation of safe space as a site for negotiating difference and challenging oppression.
Keywords: activism; intersectionality; paradoxical space; porosity; safe space; safety

Making Media Work: Cultures of Management in the Entertainment Industries - Johnson, Derek; Kompare, Derek; Santo, Avi (NYU Press, 2014)
In popular culture, management in the media industry is frequently understood as the work of network executives, studio developers, and market researchers-"the suits"-who oppose the more productive forces of creative talent and subject that labor to the inefficiencies and risk aversion of bureaucratic hierarchies. However, such portrayals belie the reality of how media management operates as a culture of shifting discourses, dispositions, and tactics that create meaning, generate value, and shape media work throughout each moment of production and consumption. Making Media Work aims to provide a deeper and more nuanced understanding of management within the entertainment industries. Drawing from work in critical sociology and cultural studies, the collection theorizes management as a pervasive, yet flexible set of principlesdrawn upon by a wide range of practitioners-artists, talent scouts, performers, directors, show runners, and more-in their ongoing efforts to articulate relationships and bridge potentially discordant forces within the media industries. The contributors interrogate managerial labor and identity, shine a light on how management understands its roles within cultural and creative contexts, and reconfigure the complex relationship between labor and managerial authority as productive rather than solely prohibitive. Engaging with primary evidence gathered through interviews, archives, and trade materials, the essays offer tremendous insight into how management is understood and performed within media industry contexts. The volume as a whole traces the changing roles of management both historically and in the contemporary moment within US and international contexts, and across a range of media forms, from film and television to video games and social media.

Putting gender in the mix: employment, participation, and role expectations in the music industries - LEONARD, MARION (The Routledge Companion to Media & Gender, 2014)
Eﬀorts to map women’s participation in the music industries have been hampered by a lack of data. However, available statistics point to a continuing underrepresentation of women in the music industries; and the disparity is particularly acute within certain areas of practice. In 2010 the Performing Rights Society for Music (PRS), the UK’s leading collection society, revealed that women accounted for only 14 percent of their registered music creators and writers. This statistic prompted the PRS Foundation to fund the “Women Make Music” initiative as a way to raise awareness of the gender gap, correct stereotypes, encourage participation, and increase the proﬁle of women creating new music. Research commissioned in 2008 by the Cultural Leadership Programme and publishedas a substantial report, found that in the UK music sector “only 20% of businesses have any form of female representation on the management team and only 10% have an all female team” (Cultural Leadership Programme 2008: 29). According to the report, women in the music sector were generally very underrepresented within positions of responsibility: the average number of female executives per ﬁrm was as low as 0.2. Such evidence of gender inequality in leadership positions within the music industries is by no means unique to the UK. In 2012 the editorial team of the Australasian Music Industry Directory (AMID), in consultation with other industry professionals, ranked for the ﬁrst time the most powerful people in the Australian music industry. The criteria included who has the greatest “ability to ‘shape’ the scene,” along with “their involvement in industry initiatives, overall career accomplishment, economic impact and public proﬁle” (Fitzsimons 2012). The “power list” included 50 places and 56 people (some business partners held joint positions). Only six women appeared on the list, two of whom shared their place with a male colleague; overall, then, women were just under 11 percent. While the list can be critiqued for its partiality, it indicates the music industries’ gender gap. Books on women working in the music industries usually focus on women musiciansand performers, often with the aim of celebrating women’s contribution to the history of popular music (see, for example, Dahl 1984; Gaar 1993; Hirshey 2001; Downes 2012). In documenting women’s experience, ﬁeld research with musicians has shownhow women have established their music careers, from acquiring instruments and learning to play, to performing and navigating the music business (see, e.g., Bayton 1998; Tucker 2000; Reddington 2007; Leonard 2007). A few speciﬁcally highlight women involved in music production and sound engineering (Sandstrom 2000; Smith 2009). Some recent work on women’s changing relationship with music technologies examines how artist-producers (Wolfe 2012) and women involved in the electronic dance music scene (Farrugia 2012) have navigated a gendered sphere of practice which has historically and discursively been associated with masculinity. Music journalism has also been a focus, with critical accounts addressing the work of women music journalists and the gendered discourse of music journalism (McDonnell 1995; Davies 2001; McLeod 2001). While the literature on women musicians, journalists, DJs, and music engineers is growing, the experience of women working in other roles within the music sector is much less well documented. Indeed, Smith (2009: 308) remarks that, except for musicianship, “scholarship on gender segregation in other music industry roles has been meagre. Because of this, the gendered division of labour in the music industry is not yet adequately understood.” This chapter explores how gendered attitudes circulate within the workplace andin what ways they frame work in diﬀerent sectors of the music industries. The plural term “music industries” suggests the chapter is not engaging with a uniﬁed ﬁeld of practice, nor is it concerned only with the recording industry (Williamson and Cloonan 2007). I will draw on interviews with eight women who have worked in artist management, tour management, A&R (artist and repertoire), and concert promotion, although ﬁrst I discuss the contexts in which these women work as a way to establish the extent to which their occupations can be broadly characterized as sex segregated. These women work in largely under-studied but particularly sex-segregated areasof music employment. All eight were based in London, England and ranged in levels of seniority from a booking agent’s assistant to a general manager of a record company. Many of the women had established portfolio careers, having worked in different roles, including radio promotion, international relations, music publishing, and marketing, so had diﬀerent levels of experience in management, A&R, and concert promotion. For example, one participant worked for two years at a junior level in A&R before moving on to develop expertise in other areas, eventually becoming a general manager of a record company. Another participant began as a regional A&R scout and was promoted to A&R manager, where she stayed ten years. Therefore, they could oﬀer a broad perspective: collectively they were engaged with international professional networks, international tour management, and the management and career development of artists building international proﬁles. The majority of them worked with rock bands and artists but some had worked with artists in other genres. The participants could also reﬂect on their experience of working with artists at diﬀerent stages of career development, from new and developing bands through to major international recording stars. Seven of the approximately hour-long interviews were conducted by telephone; their responses to the open-ended questions were recorded and transcribed. One respondent oﬀered a written response to the research questions via email. The women all seemed candid in their responses. Their comments have been anonymized; references to particular record labels, bands, or named individuals have been omitted.

A Music Room of One's Own: Discursive Constructions of Girls-only Spaces for Learning Popular Music - Björck, Cecilia (Girlhood Studies, 2013)
This article elaborates on discursive constructions of girls-only settings through the spatial metaphor of a room of one's own, as articulated in round-table discussions among staff and participants from girl-centered music programs in Sweden. The idea of a separate room refers to spaces for collective female empowerment as well as for individual knowledge acquisition and creativity. These spaces are constructed so as to provide the possibility for exploration, subjectivity, and focus, by offering (partial and temporary) escape from competition and control, from a gendered and gendering gaze, and from distraction. Girl-centered programs are also discussed as paradoxical because they function as gender-neutral when seen from the inside, but gender-specific when seen from the outside.

Safe Space: The Riot Grrrl Collection - Keenan, Elizabeth K.; Darms, Lisa (Archivaria, 2013)
Riot Grrrl, an early-1990s teen feminist movement, adopted punk’s DIY modes of expression to encourage girls to address their shared oppression. The Riot Grrrl Collection, held at New York University’s Fales Library & Special Collections, documents the movement through the personal papers of those who were active in its formative years. This article uses the lens of feminist “safe space” to look at the collection from two perspectives: that of its founder, Lisa Darms, who is senior archivist at Fales, and that of ethnomusicologist Elizabeth Keenan, a scholar who has worked extensively with the collection. The concept of safe space was crucial to the all-girl meetings, dance parties, and bands that formed the foundation of Riot Grrrl. The authors argue that the safe space of Riot Grrrl created an intimate counter-public – that is, a space where girls established a feminist community through shared texts – but one that sometimes worked against its own intentions: boundaries erected for safety sometimes led to exclusion along lines of race, class, or gender identity. The authors extend the idea of safe space to issues of collection building from and within activist communities; to ideas of intimacy and privacy as they play out for donors, for researchers, and in the special collections reading room; and to the tension between the desire for access to activist history versus the requirements of archival preservation. The article examines how iterations of safe space are enacted across the personal papers in the Riot Grrrl archive, through both the materials themselves and their place in the archive. RÉSUMÉ Riot Grrrl, un mouvement du début des années 1990 pour adolescentes féministes, s’est inspiré du mouvement punk pour adopter les modes d’expression du « Do it yourself (DIY) », dans le but d’encourager les adolescentes à aborder leur oppression commune. La collection Riot Grrrl, détenue par la Fales Library & Special Collections de l’University New York, documente le mouvement grâce aux documents personnels de celles qui en étaient actives durant ses premières années. Cet article se sert du concept féministe du « lieu sûr » (« safe space ») afin d’examiner la collection à partir de deux perspectives : celle de sa fondatrice, Lisa Darms, qui est archiviste supérieure à Fales, et celle de l’ethnomusicologue Elizabeth Keenan, une spécialiste qui a travaillé en profondeur avec cette collection. Le concept du lieu sûr était crucial pour les adolescentes lors de leurs réunions et soirées dansantes et pour leurs groupes musicaux qui ensemble ont contribué à la fondation de Riot Grrrl. Les auteurs soutiennent que le lieu sûr de Riot Grrrl a créé un « contre-public intime » – c’est-à-dire un espace dans lequel les adolescentes ont pu établir une communauté féministe par l’entremise de textes partagés – mais un contre-public qui opérait parfois contre ses propres intentions : les limites imposées pour délimiter le lieu sûr ont parfois mené vers des exclusions basées sur la race, les classes sociales ou l’identité de genre. Les auteures élargissent le concept du lieu sûr aux questions liées à la création de collections par des communautés militantes et dans ces milieux; aux idées de l’intimité et de la vie privée auxquelles sont confrontés les donateurs et les chercheurs dans la salle de lecture des collections spéciales; et à la tension entre le désir d’avoir accès à l’histoire militante et les besoins liés à la conservation archivistique. Cet article examine comment l’itération du lieu sûr se fait par rapport aux documents personnels des archives Riot Grrrl, tant du côté des documents eux-mêmes que de leur place dans les archives.

Female, Mosher, Transgressor: A 'Moshography' of Transgressive Practices within the Leeds Extreme Metal Scene - Riches, Gabrielle; Lashua, Brett; Spracklen, Karl (IASPM Journal, 2013)
This paper examines and reconceptualises transgression in the Leeds extreme metal music subculture through theories of performance, embodiment and spectacle. The spectacle, for Debord (1967), is a social relation that is alienating and mediated by images, visuals, and technology. At a live extreme metal concert fans subvert social norms, challenge gendered expectations, and disregard norms of etiquette and decency. Moshing is the most visible and sensuous example of transgression within the extreme metal scene. It is an aggressive, physically demanding performance which embodies resistance to the impersonal and disillusioning world of the spectacle (Halnon, 2004). The pit is a transgressive space that is itself transgressed by women who participate in this masculine, chaotic space, disrupting the homosocial bonds of male solidarity (Gruzelier, 2007). This paper offers an ethnographic account of a female metal fan participating in the transgressive practice of moshing within the Leeds metal music scene – a moshography.
Keywords: Moshpits; embodiment; extreme metal music; performance ethnography; spectacle; transgression

Why producers of music use discourses of consumption (and why we shouldn't think that makes them prosumers) - Cluley, Robert (Arts Marketing: An International Journal, 2013)
Purpose ‐ The purpose of this paper is to demonstrate how people making music represent their production activities using images of consumption. Design/methodology/approach ‐ Supporting evidence is based on in-depth interviews with musicians and support personnel. The data are structured through a thematic analysis. Findings ‐ The paper argues that consumption serves as a discursive resource that allows cultural producers to make sense of production activities which do not conform to an image of production as an alienated form of labour. Originality/value ‐ Relating the analysis to the ongoing attempts to conceptualise cultural producers through the concept of prosumption, the paper concludes that there are limits to cultural producers' abilities to represent their production activities as production rather than a structural change in social or economic organisation, as suggested by some consumer researchers.

Why unpaid interns are bad for the music industry (the Guardian, 2013)
Helienne Lindvall: Big US record labels are being sued by former interns who worked for free – how do their UK counterparts measure up?

Q&A: Veteran Music Video Director Diane Martel on Her Controversial Videos for Robin Thicke and Miley Cyrus - Ducker, Eric (Grantland, 2013)
Heads up: NSFW videos and websites are occasionally linked to throughout this post, so watch who’s watching your monitor. Robin Thicke’s “Blurred Lines” and Miley Cyrus’s “We Can’t Stop…

Why Music Matters - Hesmondhalgh, David (John Wiley & Sons, 2013)
Listen to David Hesmondhalgh discuss the arguments at the core of 'Why Music Matters' with Laurie Taylor on BBC Radio 4's Thinking Allowed here. In what ways might music enrich the lives of people and of societies? What prevents it from doing so? Why Music Matters explores the role of music in our lives, and investigates the social and political significance of music in modern societies. First book of its kind to explore music through a variety of theories and approaches and unite these theories using one authoritative voice Combines a broad yet theoretically sophisticated approach to music and society with real clarity and accessibility A historically and sociologically informed understanding of music in relation to questions of social power and inequality By drawing on both popular and academic talk about a range of musical forms and practices, readers will engage with a wide musical terrain and a wealth of case studies
Keywords: Music / General; Music / History & Criticism

Looking for Something New: The Provision of Popular Music Studies Degrees in the UK - Cloonan, Martin; Hulstedt, Lauren (IASPM Journal, 2013)
This article reports the findings of some commissioned research, which was conducted by the authors in 2012. The research sought to examine the extent of Popular Music Studies (PMS) undergraduate programmes in the United Kingdom, determine their key differences, report the findings and make recommendations to the funders about its future policies for PMS practitioners. We report our findings and the implications for PMS practitioners.
Keywords: Popular Music; Teaching; UK; Undergradute

Dark Side of the Tune: Popular Music and Violence - Johnson, Professor Bruce; Cloonan, Professor Martin (Ashgate Publishing, Ltd., 2013)
Written against the academically dominant but simplistic romanticization of popular music as a positive force, this book focuses on the 'dark side' of the subject. It is a pioneering examination of the ways in which popular music has been deployed in association with violence, ranging from what appears to be an incidental relationship, to one in which music is explicitly applied as an instrument of violence. A preliminary overview of the physiological and cognitive foundations of sounding/hearing which are distinctive within the sensorium, discloses in particular their potential for organic and psychic violence. The study then elaborates working definitions of key terms (including the vexed idea of the 'popular') for the purposes of this investigation, and provides a historical survey of examples of the nexus between music and violence, from (pre)Biblical times to the late nineteenth century.The second half of the book concentrates on the modern era, marked in this case by the emergence of technologies by which music can be electronically augmented, generated, and disseminated, beginning with the advent of sound recording from the 1870s, and proceeding to audio-internet and other contemporary audio-technologies. Johnson and Cloonan argue that these technologies have transformed the potential of music to mediate cultural confrontations from the local to the global, particularly through violence. The authors present a taxonomy of case histories in the connection between popular music and violence, through increasingly intense forms of that relationship, culminating in the topical examples of music and torture, including those in Bosnia, Darfur, and by US forces in Iraq and Guantánamo Bay. This, however, is not simply a succession of data, but an argumentative synthesis. Thus, the final section debates the implications of this nexus both for popular music studies itself, and also in cultural policy and regulation, the ethics of citizenship, and arguments about human rights.
Keywords: Music / Ethnomusicology; Music / Instruction & Study / Theory

The Continuum of Sexual Violence: Women’s Accounts of Victimization in Urban Nightlife - Kavanaugh, Philip R. (Feminist Criminology, 2013)
Despite the fact that a substantial amount of research has been conducted on sexual victimization among youth and young adults with active night lives, few of these studies have provided an analysis of the varied types of victimization that have occurred. I attempt to fill this gap with a qualitative analysis of women’s accounts of sexual victimization. Based on the substantive content of these women’s accounts, a three-part typology was generated, comprised of: (a) competing definitions of the situation, (b) opportunistic predation, and (c) involuntary incapacitation. Implications of the findings are discussed.
Keywords: accounts; sexual assault; sexual victimization; unwanted sexual contact

Music, Style, and Aging: Growing Old Disgracefully? - Bennett, Andy (Temple University Press, 2013)
The image of the aging rock-and-roller is not just Paul McCartney and Mick Jagger on stage in their sixties. In his timely book Music, Style, and Aging , cultural sociologist Andy Bennett explains how people move on from youth and effectively grow older with popular music.For many aging followers of rock, punk, and other contemporary popular genres, music is ingrained in their identities. Its meaning is highly personal and intertwined with the individual's biographical development. Bennett studies these fans and how they have changed over time--through fashions, hairstyles, body modification, career paths, political orientations, and perceptions of and by the next generation.The significance of popular music for these fans is no longer tied exclusively to their youth. Bennett illustrates how the music? that "mattered" to most people in their youth continues to play an important role in their adult lives--a role that goes well beyond nostalgia.

A woman's worth: Analyzing the sexual objectification of Black women in music videos - Ward, L. Monique; Rivadeneyra, Rocio; Thomas, Khia; Day, Kyla; Epstein, Marina (The sexualization of girls and girlhood: Causes, consequences, and resistance, 2013)
One arena where images of sexually objectified women are especially prevalent is the world of music videos. Music videos represent an important area of study, both because of their popularity with younger viewers (Ashby & Rich, 2005) and because love and sex predominate as themes (Andsager & Roe, 1999; Arnett, 2002). What we seek to do here is to take a closer look at the nature and impact of the portrayal of women in music videos, focusing, in particular, on sexually objectifying images. How frequently do objectifying images occur? What messages about femininity do these images convey to girls? What is their demonstrated impact on girls and young women? Given the current popularity of rap and hip-hop music, we focus our attention on their portrayals of African American women. We address these issues via four pathways. First, we summarize findings from existing research concerning the nature of gender portrayals in music videos. Second, we turn our attention to African American artists and summarize findings about the images of black women in music videos. Third, we present new data from an analysis we conducted of the sexual content in black music videos, providing both quantitative and thematic analyses. Finally, we summarize findings about the demonstrated impact of music video exposure on young viewers' gender beliefs and body image concerns. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Blacks; Human Females; Music; Myriam; Objectification; Sex Roles

Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille

Democratising the popular: the case of pop music in France and Britain - Looseley, David L. (International Journal of Cultural Policy, 2012)
The article represents the second phase of a comparative project on French and British cultural policy. The project's guiding hypothesis is that conceptualisations of the popular have been a crucial driver of policy change in France and Britain, raising complex issues about the nature of cultural democracy. The second phase, including this article, takes pop music as a case study for that hypothesis. The article explores three major issues. It asks how and why, in their attempts to rethink cultural democracy for the twenty-first century, French and British policy agencies have recognised pop music as a ‘democratic' form worthy of state support. It critically examines some of the theoretical issues this has raised, comparing and contrasting the ways in which the two national policy sets have variously represented pop as having symbolic, economic and social meanings. And it argues that what has been less adequately addressed is its aesthetic meaning.
Keywords: France and the UK; cultural democracy; pop music

Beyond the Dance Floor: Female DJs, Technology and Electronic Dance Music Culture - Farrugia, Rebekah (Intellect Books, 2012)
A pathbreaking study of the women who create electronic dance music, Beyond the Dance Floor focuses on the largely neglected relationship between these women and the conceptions of gender and technology that continue to inform the male-dominated culture surrounding electronic music. In this volume, Rebekah Farrugia explores a number of important issues, including the politics of identity and representation, the bonds formed by women within the DJ community and the role female DJs and producers play in this dance music culture as well as in the larger public sphere. Though Farrugia primarily focuses on women's relationship to music-related technologies – including vinyl, mp3s and digital production software – she also deftly extends her argument to the strategic use of the Internet and web design skills for purposes tied to publicity, networking and music distribution.
Keywords: Music / Genres & Styles / Electronic; Performing Arts / Dance / General; Social Science / Popular Culture; Social Science / Women's Studies; Technology & Engineering / General

The Expansion of Punk Rock: Riot Grrrl Challenges to Gender Power Relations in British Indie Music Subcultures - DOWNES, JULIA (Women's Studies, 2012)

'Rock On': Women, ageing and popular music - Jennings, R.; Gardner, Abigail ('Rock On': Women, Ageing and Popular Music, 2012)
For female pop stars, whose star bodies and star performances are undisputedly the objects of a sexualized external gaze, the process of ageing in public poses particular challenges. Taking a broadly feminist perspective, 'Rock On': women, ageing and popular music shifts popular music studies in a new direction. Focussing on British, American and Latina women performers and ageing, the collection investigates the cultural work performed by artists such as Shirley Bassey, Petula Clark, Madonna, Celia Cruz, Grace Jones and Courtney Love. The study crosses generations of performers and audiences enabling an examination of changing socio-historical contexts and an exploration of the relationships at play between performance strategies, star persona and the popular music press. For instance, the strategies employed by Madonna and Grace Jones to engage with the processes and issues related to public ageing are not the same as those employed by Courtney Love or Celia Cruz. The essays in this insightful collection reflect on the ways that artists and fans destabilise both the linear trajectories and the compelling weight of expectations regarding ageing by employing different modalities of resistance through persona re-invention, nostalgia, postmodern intertextuality and even early death as the ultimate denial of age.

The Lost Women of Rock Music: Female Musicians of the Punk Era - Reddington, Helen (Equinox Pub., 2012)
In the late 1970s and early 1980s a new phenomenon emerged in UK popular music - female guitarists, bass-players, keyboard-players and drummers began playing in bands. Before this time, women's presence in rock bands, with a few notable exceptions, had always been as vocalists. This sudden influx of female musicians into the male domain of rock music was brought about by the enabling ethic of punk rock ('anybody can do it ') and by the impact of the Sex Discrimination Act. With the demise of the punk scene, interest in these musicians evaporated and other priorities became important to music audiences. This book investigates the social and commercial reasons why these women became lost from the rock music record, and rewrites this period of popular music history. In addition to a wealth of original interview material with key protagonists, including the late John Peel, Geoff Travis, The Raincoats and Poison Girls, this new edition has been updated to include interviews with members of Birmingham-based band The Au Pairs, Leeds-based band Delta 5 and Viv Albertine of The Slits. Lucy Whitman (aka Lucy Toothpaste), who started the fanzine Jolt and later wrote for Spare Rib, also provides enlightening words on the relationship between female punk band members and feminism. The author also draws on her own experience as bass-player in a punk band.
Keywords: Music / Genres & Styles / Punk; Music / History & Criticism; Social Science / Women's Studies

Notions of popular culture in cultural policy: a comparative history of France and Britain - Looseley, David (International Journal of Cultural Policy, 2011)
The Devlin and Hoyle report, Committing to culture: arts funding in France and Britain, argues that the cultural policies of these two European neighbours have been steadily converging since the mid‐1990s but that their social and economic contexts are now quite different (e.g. youth unemployment, GDP, disposable income). The paper addresses this convergence‐within‐divergence by comparing how policy discourses have conceptualised popular culture in the two countries. It investigates the hypothesis that, in both, an engagement with popular culture has in fact been an important driver of change, albeit at different times and with different taxonomies. And it asks what light this comparison might shed on cultural policy thinking in the twenty‐first century.
Keywords: France; UK; cultural policy; history; popular culture

‘Guys! Stop Doing It!’: Young Women's Adoption and Rejection of Safety Advice when Socializing in Bars, Pubs and Clubs - Brooks, Oona (The British Journal of Criminology, 2011)
Concern about the increase in alcohol consumption amongst young women, drink spiking and drug-assisted sexual assault have culminated in a renewed focus on safety advice for young women. This paper examines young women's responses to safety advice, and their associated safety behaviours, by drawing upon interview and focus group data from a qualitative study with 35 young women (18–25 years) in relation to their safety in bars, pubs and clubs. The findings reveal that young women's behaviours were complex and contradictory in that they resisted, adopted and transgressed recommended safety behaviours. This raises interesting questions about both the practical and the theoretical implications of contemporary safety campaigns, challenging the prevailing focus on women's behaviour and the gendered discourse invoked by such campaigns.

Music festival sponsorship: between commerce and carnival - Anderton, Chris (Arts Marketing: An International Journal, 2011)
Purpose – This paper aims to examine the cultural heritage of outdoor rock and pop music festivals in Britain since the mid‐1960s, and relates it to developments in, and critiques of, corporate sponsorship in the contemporary music festival sector. Design/methodology/approach – The paper uses extant research materials to construct an account of British music festival history since the mid‐1960s. It then draws upon Bakhtin's concept of the carnivalesque and the literature on sponsorship, experiential marketing and branding, in order to understand critiques of corporate sponsorship and the changing nature of the sector. Findings – Outdoor rock and pop music festivals were dominated by the ideologies of a “countercultural carnivalesque” from the late 1960s until the mid‐1990s. In the 1990s, changes in legislation began a process of professionalization, corporatization, and a reliance on brand sponsorships. Two broad trajectories are identified within the contemporary sector: one is strongly rooted in the heritage of the countercultural carnivalesque, while the other is more overtly commercial. Research limitations/implications – It is argued that experiential marketing and brand activation are key methods for achieving a balance between the competing aspects of commerce and carnival. Hence, festival organisers and sponsors need to understand the history of the sector and of their own events and attendees in order to use corporate sponsorship more effectively. Originality/value – This paper adds historical and theoretical depth to the debate between commerce and carnival within the music festival sector, and makes connections between cultural theory and the literature on sponsorship and branding.
Keywords: Bakhtin; Branding; Carnivalesque; Counterculture; Music festivals; Sponsorship; United Kingdom

Popular Music and the State in the UK. Culture, Trade or Industry? by Martin Cloonan - Laing, Dave (Popular Music, 2011)

Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture - Strong, C. (2011)
Semantic Scholar extracted view of "Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture" by C. Strong

Domestic and Sexual Violence and Abuse: Tackling the Health and Mental Health Effects - Itzin, Catherine; Taket, Ann; Barter-Godfrey, Sarah (Routledge, 2010)
Domestic violence, childhood sexual abuse, rape and sexual assault, and sexual exploitation through prostitution, pornography and trafficking can have many significant adverse impacts on a survivor’s health and wellbeing, in the short, medium and long-term. Taking a life-course approach, the book explores what is known about appropriate treatment responses to those who have experienced, and those who perpetrate, domestic and sexual violence and abuse. The book also examines key factors that are important in understanding how and why different groups experience heightened risks of domestic and sexual violence and abuse, namely: gender and sexuality; race and culture; disability; and abuse by professionals. Drawing together results from specially commissioned research, the views of experts by experience, experts by profession and the published research literature, the book argues that sufficient is already known to delineate an appropriate public health framework, encompassing primary, secondary and tertiary prevention, to successfully tackle the important public health issue represented by domestic and sexual violence and abuse. Domestic and Sexual Violence and Abuse equips health and social care professionals and services to identify and respond to the needs of affected individuals with a view to the prevention and early intervention.
Keywords: FAMILY & RELATIONSHIPS; Family & Relationships / Abuse / Child Abuse; Family & Relationships / Abuse / General; Health & Fitness / Women's Health; Medical / Allied Health Services / General; Medical / Health Care Delivery; Psychology / Mental Health; Social Science / Sexual Abuse & Harassment; Social Science / Social Work; Social Science / Violence in Society

Music Education in the 21st Century in the United Kingdom: Achievements, Analysis and Aspirations - Hallam, Susan; Creech, Andrea Ed (Institute of Education - London, 2010)
The landscape of music education in the UK is constantly shifting and developing. This book provides a timely and unique overview of this restless sector by considering the achievements of music education, analysing its current performance and setting out aspirations for the future. "Music Education in the 21st Century in the United Kingdom" addresses the power of music to influence and change human behaviour, analyses current and future issues in music education and casts a spotlight on particular areas of education, including early years, the primary school, the secondary school, further education, universities and conservatoires, music services, the music studio and the role of music leaders and community musicians. Written by experts in the field of music education, the book provides an authoritative account of the current status of music education in the UK. While essential to understand the current and future context in the UK, the book will be invaluable to those involved in music education internationally, as it includes chapters on the provision of music education for all children, listening, the role of singing, playing an instrument, creativity, the role of technology, issues of performance and assessment, learning through the lifespan and the initial and ongoing education of music teachers. It also includes a range of case study examples and evaluations of practice. The book is a landmark publication in the field of music education and will be essential reading for policy-makers, practitioners, music students, trainee music teachers and those who provide music services in the UK and internationally. This book contains three parts. Part I, "Introduction", contains: (1) The power of music: its impact on the intellectual, personal and social development of children and young people (Susan Hallam); and (2) Contextualising music education in the UK (Pauline Adams, Hilary McQueen, and Susan Hallam). Part 2, "Current Issues in Music Education", contains: (3) Music for all (Graham Welch and Adam Ockelford); (4) Listening (Susan Hallam); (5) The role of singing (Jo Saunders, Maria Varvarigou and Graham Welch); (6) Learning to play an instrument (Susan Hallam and Andrea Creech); (7) Creativity (Susan Hallam and Lynne Rogers); (8) The role of technology (Evangelos Himonides and Ross Purves); (9) Issues of assessment and performance (Ioulia Papageorgi and Susan Hallam); (10) Learning through life (Hilary McQueen and Maria Varvarigou); and (11) The initial and ongoing education of music teachers (Colin Durrant and Kate Laurence). Part 3, "Contexts of Learning", contains: (12) Music in the early years (Andrea Creech and Jessica Ellison); (13) Music in the primary school (Jessica Ellison and Andrea Creech); (14) Music in the secondary school (Hilary McQueen and Susan Hallam); (15) Music in further education colleges (John Conlon and Lynne Rogers); (16) Music in universities and conservatoires (Helena Gaunt and Ioulia Papageorgi); (17) Music Services (Lynne Rogers and Susan Hallam); (18) The music studio (Andrea Creech); (19) The role of music leaders and community musicians (Andrea Creech); and (20) Where now? (Susan Hallam and Andrea Creech). This book also contains: Acknowledgements; Preface; Notes on contributors; and Index.
Keywords: Adult Education; Creativity; Early Childhood Education; Educational Trends; Elementary Education; Evaluation; Foreign Countries; Futures (of Society); Higher Education; Individual Development; Inservice Teacher Education; Intellectual Development; Leaders; Lifelong Learning; Listening; Music Education; Music Teachers; Musical Instruments; Musicians; Performance; Preservice Teacher Education; Secondary Education; Singing; Social Development; Technology Uses in Education

Comparative Gender and Institutions: Directions for Research - Chappell, Louise (Perspectives on Politics, 2010)
A comparative politics of gender offers an opportunity to consider in detail the operation of gender within political institutions. As such, it contributes to a deeper understanding of the roles and experiences of men and women within political institutions, of the policies, laws and norms that are the outcomes of these institutions, and of the relationship between these institutions and social actors. This essay proposes a multi-directional strategy for undertaking comparative gender and institutional research that includes taking account of similarities and differences within and across states, between states and international institutions, across space as well as across time. It argues that through this research strategy it is possible to gain a more nuanced understanding of gender processes and outcomes, which is valuable to those working both inside and outside political institutions to advance a women's equality agenda.